Livestock production in tsetse affected areas of Africa. Proceedings of a meeting - International Livestock Centre for Africa (International Livestock Centre for Africa, 1988)
Presents papers dealing with various aspects of livestock production in tsetse affected areas of Africa, particular tsetse challenge, trypanosomiasis epidemiology, trypanotolerance, biological productivity, chemotherapy, economics, and genetics of trypanotolerance.